Analyzing risk factors for lumpy skin disease by a geographic information system (GIS) in Turkey - INCE, O.B.; TÜRK, T. (Journal of the Hellenic Veterinary Medical Society, 2020)
Lumpy skin disease (LSD) is caused by the virus of the same name and has major economic impacts on cattle breeding. In Turkey, frequent cases of cattle LSD have been reported over the last years. The present study aimed to analyze potential risk factors for LSD and provide information for controlling the spread of infectious diseases by a geographic information system (GIS). The research included cross-sectional and retrospective studies with active disease follow-up and semi-structured interviews (SSI) from August 2013 to December 2014 in Turkey. Potential risk factors for LSD were evaluated based on environmental conditions and provincial demographic and epidemiological data. Of the total of 562 observed animals, 27.22% and 2.67% of cattle were sick and died due to LSD, respectively. The morbidity rate was 26.04% in mixed and 38.18% in local breeds. The animal-level prevalence significantly differed among animals of different age, sex, and with different vaccination status (P<0.05). It was more serious in younger animals and females and during drier weather conditions. A trend of seasonality was observed in LSD occurrence. Significant risk factors affecting the prevalence of LSD were proximity to the southern border of Turkey, animal movements, and animal markets. In this process, geographical query, analysis, and thematic map production were performed by GIS.